Literature analysis of the emotional colours in big brand logo design / Nik Nahdiya Nik Kamaruzaman and Marhainis Jamaludin - Nik Kamaruzaman, Nik Nahdiya; Jamaludin, Marhainis
Every brand proclaims its own identity through its logo. Any logo has its vision, whether through symbols, shapes, or colours. One of its colour features is that colours play a vital role in directing the immediate emotional responses of the viewers. Nonetheless, little academic research has explored the effect of colours in the logo design of big brands that manage to grasp people's attention and retain their memory for the longest time. This paper analyses the research on colours and emotions articulated by logo designs using colour theory. The author explored the emotional resonance of colours in the logo design of big brands and linked it with several computer techniques applied to detect emotional colours. The result reveals a connection between colours' emotions and the essence of their brands; colours do portray distinctive emotions related to their brand identity, hence several techniques could assist in that mission. Towards the end, the study noted that the other brands, particularly the new ones, should be explicitly particular in choosing the colours for their brands to hold people's memories.